2003
DOI: 10.1002/cncr.11200
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II trial of green tea in the treatment of patients with androgen independent metastatic prostate carcinoma

Abstract: BACKGROUNDRecent laboratory and epidemiologic studies have suggested that green tea has antitumor effects in patients with prostate carcinoma. This Phase II trial explored green tea's antineoplastic effects in patients with androgen independent prostate carcinoma.METHODSThis study, which was conducted by the North Central Cancer Treatment Group, evaluated 42 patients who were asymptomatic and had manifested, progressive prostate specific antigen (PSA) elevation with hormone therapy. Continued use of luteinizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
149
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(153 citation statements)
references
References 14 publications
3
149
0
1
Order By: Relevance
“…Only one patient manifested a decline in serum PSA, and no patient manifested a tumor response on radiographic assessment or physical examination. Thus, a limited antineoplastic effect with a maximum response rate of 2% was seen with green tea [24]. Similar results were observed in another clinical trial involving patients with hormone refractory CaP.…”
Section: Green Teasupporting
confidence: 85%
See 1 more Smart Citation
“…Only one patient manifested a decline in serum PSA, and no patient manifested a tumor response on radiographic assessment or physical examination. Thus, a limited antineoplastic effect with a maximum response rate of 2% was seen with green tea [24]. Similar results were observed in another clinical trial involving patients with hormone refractory CaP.…”
Section: Green Teasupporting
confidence: 85%
“…A case control study, conducted in southeast China during 2001 to 2002, reported a reduced CaP risk with increasing frequency, duration, and quantity of green tea consumption [23]. In another study, patients with asymptomatic androgen-independent metastatic prostate carcinoma and progressive PSA elevation were evaluated after ingestion of 6 g of green tea per day [24]. Only one patient manifested a decline in serum PSA, and no patient manifested a tumor response on radiographic assessment or physical examination.…”
Section: Green Teamentioning
confidence: 99%
“…In subsequent studies, Jatoi et al [177] and Luo et al [178] have described an antineoplastic activity in terms of biomarkers: diminished PSA levels [177] and decreased urinary 8-hydroxydeoxyguanosine [178] in patients with prostate and hepatic cancer, respectively. In these trials, patients with prostate cancer received 6 g of green tea per day in six divided doses [177], and four capsules daily containing either 500 or 1000 mg of green tea polyphenols were administrated to the patients with liver cancer [178].…”
Section: Polyphenols and Clinical Trialsmentioning
confidence: 99%
“…demonstrated that green tea extracts (GTE) are more effective when feeding (0.1% in drinking water) is started at very early stages of PCa development (presence of "in situ" histological lesions) while the chemopreventive potential decreases in animals bearing tumors of more advanced stage, finally resulting largely ineffective in animals that display moderately differentiated adenocarcinoma and occasionally metastasis [143]. To reinforce the concept that GTCs are ineffective as chemotherapeutic molecules, very limited or no effects have been observed in patients with advanced PCa [144][145][146]. At difference, we introduced for first the "Proof of Concept" that secondary chemoprevention of PCa with GTCs is feasible [17].…”
Section: Gtcs In Human Pca Chemoprevention: From Epidemiological Datamentioning
confidence: 99%